Efeitos cardiovasculares do treinamento intervalado de alta intensidade na cardiotoxicidade induzida por doxorrubicina em ratos - Lopes, Leandro Teixeira Paranhos (2018)
Introduction: Doxorubicin (DOXO) is a drug belonging to the anthracycline group often used as part of the treatment of several tumors. While low intensity exercise has been shown to be cardioprotective, cardiac function and structure response under the influence of high intensity interval training (HIIT) is not clearly established. Objective: to analyze the effect of HIIT on the function and preservation of cardiac structure after administration of doxorubicin. MATERIALS AND METHODS: Thirty-six rats were randomly assigned to the control group-C (n = 8), doxorubicin-D (n = 10), doxorubicin and HIIT-DE (n = 9) and HIIT-E (n = 9). The rats of groups D and DE received DOXO for two weeks and the groups DE and E performed HIIT for four weeks. At the end of this period, body weight, heart weight, ejection fraction and LV shortening (LVEF and FS), collagen and cardiomyocyte diameter were evaluated. Results: Body weight related to body weight was lower in group E. HR was lower in the groups with doxo administration being accentuated with exercise with LVEF and FS being preserved with exercise and reduced with doxo administration. The diameters of the cardiomyocytes did not change, but there was a change in the collagen in group D. Conclusion: The high-intensity interval training performed after administration of doxorubicin in Wistar rats is able to preserve cardiac function and structure after administration of doxorubicin.